Strategi Pemerintah Indonesia untuk Mempertahankan Kedaulatan di Wilayah Kepulauan Natuna Tahun 2009-2017 - Indra Pandapotan; Subhilhar Subhilhar; Heri Kusmanto (Universitas Negeri Medan, 2019)
As a country whose waters are wider than the land, Indonesia must deal with threats that occur in Indonesian waters. In 2009, the Indonesian EEZ in the Natuna Islands was unilaterally claimed by the Chinese government on a map containing nine imaginary lines. The focus of this research is the analysis of threats that occur in the Natuna Islands and the Indonesian government's strategies in maintaining the sovereignty of the Natuna Islands. This type of research is descriptive-analytical, that trying to describe various situations, conditions that exist in society that are the object of research. In this study also uses theories and concepts that can be used as a guide in conducting research. These theories are Morgenthau's National Interest Theory, Soft Power Theory put forward by Nye, and the Concept of Defense and Security. The results of this study are that in maintaining the sovereignty of the Natuna Islands, the Indonesian government applies two strategies, namely diplomatic and defense strategies. Among these two strategies, a strategy that is quite successful in maintaining the sovereignty of the Natuna Islands is a defense strategy.